Information Needs and Seeking Behaviour of Nurses in Some Selected Hospitals in Ekpoma, Edo State, Nigeria - Onyia , Gladys Ngozi; C. L. N., Osaheni Oni (International Journal For Research In Health Sciences And Nursing, 2016)
This study investigated the information seeking behaviour of nurses in hospitals in Ekpoma, Edo state. A descriptive survey design was adopted and questionnaire was the instrument used to obtain data. Thirty copies (30) of the questionnaires were distributed, returned completed and used for the study. Four (4) research questions were raised. The data collected were analyzed through the use of simple descriptive analysis of frequency counts, percentages and mean. The stated findings of this study are that most nurses in hospitals in Ekpoma need information in the area of diagnosis, drug therapy, health development/current medical treatment and medical information on the Internet. Frequent power outage, high cost information resources, lack of search skills, high cost of internet access, inadequate materials in library, lack of adequate time, no nearby library and slow internet response are the major challenges militating against information needs of nurses in hospitals in Ekpoma. The study recommends that government should engage Internet service providers in dialogue to proffer solution to the high cost of Internet accessibility, poor network and bandwidth that is preventing vast majority of the citizenry including nurses’ smooth access to current information and nurses on their own should create time for research and self development. Knowing full well that, current information is an essential ingredient to effective service delivery.